2016
DOI: 10.1016/j.catena.2015.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of biological soil crusts on the slope of the Chinese Loess Plateau based on canonical correspondence analysis

Abstract: Biological soil crusts (BSCs) are a living ground cover widely distributed in arid and semi-arid regions, and providing important ecological functions in arid and semi-arid ecosystems. An understanding of the spatial distribution patterns of BSCs is foundational for the scientific management of this resource. In this study, a typical slope was selected from a small watershed, Liudaogou, in the wind-water erosion crisscross region of the Loess Plateau in northwest China. The spatial distribution characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Although some of the habitats obtained similar amounts, large differences in the dew duration took place, explaining in turn the variable species composition and biomass of the lithobionts at these habitats (Kappen et al, 1980;Kidron, 2000a;Kidron et al, 2011). Interestingly, wetness duration was also found to explain biocrust biomass and species composition, However, in the case of soil biocrusts, this wetness duration results from rain, as shown for the Negev (Kidron, Vonshak, & Abeliovich, 2009;Kidron, Vonshak, Dor, Barinova, & Abeliovich, 2010) and for the Chinese Loess Plateau (Bu et al, 2016).…”
Section: The Daily Course Of Nrw: Accumulation and Evaporationmentioning
confidence: 99%
“…Although some of the habitats obtained similar amounts, large differences in the dew duration took place, explaining in turn the variable species composition and biomass of the lithobionts at these habitats (Kappen et al, 1980;Kidron, 2000a;Kidron et al, 2011). Interestingly, wetness duration was also found to explain biocrust biomass and species composition, However, in the case of soil biocrusts, this wetness duration results from rain, as shown for the Negev (Kidron, Vonshak, & Abeliovich, 2009;Kidron, Vonshak, Dor, Barinova, & Abeliovich, 2010) and for the Chinese Loess Plateau (Bu et al, 2016).…”
Section: The Daily Course Of Nrw: Accumulation and Evaporationmentioning
confidence: 99%
“…Canonical correlation analysis (CCA) is a sorting method based on a single-peak model that combines correspondence analysis and multivariate regression analysis in the sorting process (Ter Braak 1986;Li et al 2017) and is thus capable of presenting the quadrats, the study object and the sorting results for the environmental factors on the same plot (Bu et al 2016). In this paper, because the study object is a type variable, we added three virtual variables and converted the four vegetation types to quantitative variables.…”
Section: Analysis Methodsmentioning
confidence: 99%
“…Slope was the most prominent of those factors, causing a considerable decline in biocrust cover with increasing slope. This finding was explained by their decreasing ability to fix themselves on the soil surface at high slope angles and thus their tendency to erode from the soil surface when large surface water flows occur during rainfall events (Chamizo et al, 2013;Bu et al, 2016). Thus, the surface-protecting effect of biocrusts decreases at steep plantation sites and during heavy monsoon rainfall events, which frequently occur in the broader research area in Jiangxi Province, PR China (Yang et al, 2013;Goebes et al, 2015).…”
Section: Temporal Development Of Biocrust Covermentioning
confidence: 99%
“…Biocrust cover varies across spatial scales (from centimetres to kilometres), and it could be shown that it depends not only on the surrounding vascular vegetation cover but also on soils, geomorphology, and (micro-)topography or terrain (Evans and Johansen, 1999;Ullmann and Büdel, 2003;Kidron et al, 2009;Bowker et al, 2016) in arid, semi-arid, temperate and boreal environments. Different biocrust distributions have been related to elevation and terrain-influenced microclimatic gradients (Kutiel et al, 1998), different geomorphic zones (Eldridge, 1999), varying aspects (George et al, 2000 and soil types (Bu et al, 2016). We assume that this is also true for mesic subtropical forest environments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation